(untitled) (The Review of Diabetic Studies, 2024)
Background: Drug–nutrient interactions (DNIs) occur when food, nutrients, or dietary supplements alter drug absorption, metabolism, distribution, or excretion, potentially compromising therapeutic efficacy or increasing toxicity. Healthcare professionals — especially nurses and pharmacists — are pivotal in identifying and managing DNIs through clinical nutrition care. This study aims to assess the awareness, knowledge, attitudes, and self-reported practices related to DNIs among nurses and pharmacists in Saudi Arabia. Methods: A multicenter cross-sectional study was conducted using a structured self-administered questionnaire with four dimensions: knowledge, attitudes, practices, and perceived training needs. The survey was distributed to licensed nurses and pharmacists in hospitals across Saudi Arabia. Statistical analysis included descriptive and comparative tests. Results: Of 420 respondents (250 nurses; 170 pharmacists), mean knowledge scores were moderate (nurses: 58%; pharmacists: 72%). Attitude toward the clinical importance of DNIs was high among both groups (>85%). However, the routine practice of DNI screening was low (37% nurses; 49% pharmacists). Significant differences were observed between professions (p < 0.05). Conclusions: Awareness of DNIs among Saudi nurses and pharmacists is positive but characterized by knowledge gaps and suboptimal practice, highlighting a need for targeted education and interprofessional protocols.